Involvement of TSP1 and MMP9/NGAL in Angiogenesis during Orthodontic Periodontal Remodeling - Petra Surlin; Isabela Silosi; Anne Marie Rauten; Manole Cojocaru; Lili Foia (The Scientific World Journal)
In the present study the aim was to measure the levels of Thrombospondin-1 (TSP1) and Lipocalin-2/matrix metalloproteinase 9 (MMP9/NGAL) complex in gingival crevicular fluid (GCF) at different time points of orthodontic treatment, to determine the relationship between these values and those of total-matrix metalloproteinase 9 (MMP9) and theirs implication in angiogenesis balance, in the situation of a good control of the bacterial plaque, emphasizing the role of TSP1 and MMP9/NGAL complex. GCF samples were collected from 16 young orthodontic patients requiring upper canine distalization (test tooth) with first premolar extraction. The contralateral canine (control tooth) was free from orthodontic force. For the orthodontic appliance, brackets Roth 0.018 inch with 0.012 inch NiTi archwire and a laceback were used. TSP1, MMP9/NGAL, and MMP9 increased from 1 hour before activation of orthodontic appliance to a maximum at 8 hours for MMP9 and 72 hours for MMP9/NGAL and TSP1. The results show a change in time of TSP1, MMP9/NGAL, and MMP9 levels in GCF of patients with this method of orthodontic treatment. The powerful correlation of MMP9/NGAL with TSP1 suggests their stronger involvement in angiogenesis processes in PDL during orthodontic periodontal remodeling, in the situation of a healthy periodontium and a good control of the bacterial plaque.